Step * 1 2 of Lemma monotone-bar-induction2


1. n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ ℙ
2. n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ ℙ
3. ∀n:ℕ. ∀s:ℕn ⟶ ℕ.  (B[n;s]  (∀m:ℕB[n 1;s.m@n]))
4. ∀n:ℕ. ∀s:ℕn ⟶ ℕ.  (B[n;s]  ⇃(Q[n;s]))
5. ∀n:ℕ. ∀s:ℕn ⟶ ℕ.  ((∀m:ℕ. ⇃(Q[n 1;s.m@n]))  ⇃(Q[n;s]))
6. ∀alpha:ℕ ⟶ ℕ. ∃m:ℕB[m;alpha]
7. alpha:(ℕ ⟶ ℕ) ⟶ ℕ
8. ∀alpha:ℕ ⟶ ℕB[F alpha;alpha]
9. ⇃(∃M:n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ (ℕn?)
      ∀f:ℕ ⟶ ℕ
        ∃n:ℕ(F f < n ∧ ((M f) (inl (F f)) ∈ (ℕ?)) ∧ (∀m:ℕ((↑isl(M f))  ((M f) (inl (F f)) ∈ (ℕ?))))))
10. (∃M:n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ (ℕn?)
      ∀f:ℕ ⟶ ℕ
        ∃n:ℕ(F f < n ∧ ((M f) (inl (F f)) ∈ (ℕ?)) ∧ (∀m:ℕ((↑isl(M f))  ((M f) (inl (F f)) ∈ (ℕ?))))))
 ⇃(Q[0;λx.⊥])
⊢ ⇃(Q[0;λx.⊥])
BY
((BLemma `prop-truncation-quot` THENA Auto)
   THEN RenameVar `f' (-1)
   THEN RenameVar `M' (-2)
   THEN UseWitness ⌜M⌝⋅
   THEN newQuotientElim1 (-2)⋅
   THEN Auto) }


Latex:


Latex:

1.  B  :  n:\mBbbN{}  {}\mrightarrow{}  (\mBbbN{}n  {}\mrightarrow{}  \mBbbN{})  {}\mrightarrow{}  \mBbbP{}
2.  Q  :  n:\mBbbN{}  {}\mrightarrow{}  (\mBbbN{}n  {}\mrightarrow{}  \mBbbN{})  {}\mrightarrow{}  \mBbbP{}
3.  \mforall{}n:\mBbbN{}.  \mforall{}s:\mBbbN{}n  {}\mrightarrow{}  \mBbbN{}.    (B[n;s]  {}\mRightarrow{}  (\mforall{}m:\mBbbN{}.  B[n  +  1;s.m@n]))
4.  \mforall{}n:\mBbbN{}.  \mforall{}s:\mBbbN{}n  {}\mrightarrow{}  \mBbbN{}.    (B[n;s]  {}\mRightarrow{}  \00D9(Q[n;s]))
5.  \mforall{}n:\mBbbN{}.  \mforall{}s:\mBbbN{}n  {}\mrightarrow{}  \mBbbN{}.    ((\mforall{}m:\mBbbN{}.  \00D9(Q[n  +  1;s.m@n]))  {}\mRightarrow{}  \00D9(Q[n;s]))
6.  \mforall{}alpha:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}.  \mexists{}m:\mBbbN{}.  B[m;alpha]
7.  F  :  alpha:(\mBbbN{}  {}\mrightarrow{}  \mBbbN{})  {}\mrightarrow{}  \mBbbN{}
8.  \mforall{}alpha:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}.  B[F  alpha;alpha]
9.  \00D9(\mexists{}M:n:\mBbbN{}  {}\mrightarrow{}  (\mBbbN{}n  {}\mrightarrow{}  \mBbbN{})  {}\mrightarrow{}  (\mBbbN{}n?)
            \mforall{}f:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}
                \mexists{}n:\mBbbN{}
                  (F  f  <  n  \mwedge{}  ((M  n  f)  =  (inl  (F  f)))  \mwedge{}  (\mforall{}m:\mBbbN{}.  ((\muparrow{}isl(M  m  f))  {}\mRightarrow{}  ((M  m  f)  =  (inl  (F  f)))))))
10.  (\mexists{}M:n:\mBbbN{}  {}\mrightarrow{}  (\mBbbN{}n  {}\mrightarrow{}  \mBbbN{})  {}\mrightarrow{}  (\mBbbN{}n?)
            \mforall{}f:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}
                \mexists{}n:\mBbbN{}
                  (F  f  <  n  \mwedge{}  ((M  n  f)  =  (inl  (F  f)))  \mwedge{}  (\mforall{}m:\mBbbN{}.  ((\muparrow{}isl(M  m  f))  {}\mRightarrow{}  ((M  m  f)  =  (inl  (F  f)))))))
{}\mRightarrow{}  \00D9(Q[0;\mlambda{}x.\mbot{}])
\mvdash{}  \00D9(Q[0;\mlambda{}x.\mbot{}])


By


Latex:
((BLemma  `prop-truncation-quot`  THENA  Auto)
  THEN  RenameVar  `f'  (-1)
  THEN  RenameVar  `M'  (-2)
  THEN  UseWitness  \mkleeneopen{}f  M\mkleeneclose{}\mcdot{}
  THEN  newQuotientElim1  (-2)\mcdot{}
  THEN  Auto)




Home Index